How Does Social Behavior Relate to Both Grades and Achievement Scores? - DeVries, Jeffrey M.; Rathmann, Katharina; Gebhardt, Markus (Frontiers in Psychology, 2018)
Prosocial behavior and peer problems are an important correlate of academic development; however, these effects vary by achievement measures and social behaviors. In this paper, we examined data from the German National Education Panel Study (NEPS), and we use structural equation modeling (SEM) to model the effects of prosocial behavior and peer problems on grades and competencies for both math (n = 4,132) and reading (n = 2,460) in grades 5 and 7. Our models account for the moderating effect of both gender and socioeconomic status (SES). We conclude that social behaviors relate to grades more strongly than competencies, that peer problems relate more strongly to achievement than prosocial behavior, and that the relationship is weaker in later grades. We discuss the implication that grades and achievement tests are not interchangeable measures for educators and researchers.